Growth of Multilayers of Ionic Liquids on Au(111) Investigated by Atomic Force Microscopy in Ultrahigh Vacuum - Meusel, Manuel; Lexow, Matthias; Gezmis, Emine; Bayer, Andreas; Maier, Florian; Steinrück, Hans-Peter (Langmuir, 2020)
Understanding the growth of ultrathin films of ionic liquids (ILs) on metal surfaces is of highest relevance for a variety of applications. We present a detailed study of the growth of the wetting layer and successive multilayers of 1,3-dimethylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([C1C1Im][Tf2N]) on Au(111). By atomic force microscopy (AFM) in ultrahigh vacuum, we follow the temperature-dependent behavior between 110 and 300 K at defined coverages. We initially observe the formation of a wetting layer with a thickness of ∼0.37 nm with anions and cations arranged in a checkerboard structure. Stable AFM imaging up to 280 K allows us to follow the IL growing on top of the wetting layer in bilayers with an average thickness of ∼0.71 nm, that is, double the height of the wetting layer, in a bilayer-by-bilayer fashion. This growth behavior is independently confirmed from the surface morphology, as deduced from AFM and angle-resolved X-ray photoelectron spectroscopy. High-resolution AFM images at 110 K allow for identifying the molecular surface structure of the bilayers as a striped phase, which is one of the phases also seen for the wetting layer (Meusel, M.; Lexow, M.; Gezmis, A.; Schotz, S.; Wagner, M.; Bayer, A.; Maier, F.; Steinrück, H. P. Atomic Force and Scanning Tunneling Microscopy of Ordered Ionic Liquid Wetting Layers from 110 K up to Room Temperature. ACS Nano2020, 14, 9000-9010).
CRIS-Team Scopus Importer:2020-11-27